A new information about a psychometric properties of the Polish version Bem Sex Role Inventory (called IPP in Polish) - Korzeń, Renata (Studia Psychologica: Theoria et praxis, 2006)
The paper presents a psychometric analysis of the Polish version Bem Sex Role Inventory (called IPP in Polish) made several years after it had been elaborated. IPP is being used to measure gender schema: sex-typed, cross-sex-typed, undifferentiated and androgynous. The participants (327 female and 306 male, students of Warsaw high schools) filled in IPP. Despite changes in feminine and masculine traits over time, IPP may still be a valid instrument for assessing gender-schema.